An enquiry into gamefarming in the Cape Province - Colvin, Ian Stuart (Department of Environmental and Geographical Science, 2016)
Gamefarming in Africa has generally failed to exploit the potential biological productivity of indigenous wildlife populations. This study enquired as to the reasons for such failure within the Cape Province. The enquiry focused on management, research and marketing aspects of gamefarming. Personal interviews, a questionnaire and a literature analysis provided the information for the study. A description of the overall gamefarming situation is provided. Those management problems identified here found to be largely dependent on individual farmer's methods and the intensity of game utilisation. The primary uses of game were aesthetic appreciation and sport hunting. Such usages, being of low intensity, were accompanied by low levels of management effort. The lack of a stable economic incentive was found to be the major inhibition against adopting intensive commercial means of game utilisation by cropping, safari hunting and live sale.